A construção do escândalo político midiático na Folha de S. Paulo: uma análise dos seis escandâlos envolvendo ministros do primeiro mandato do governo Dilma Rousseff (2011-2014) - Marques, Vitor William [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This dissertation analyzes the construction of mediatic political scandal in the journalistic discourse of Folha de S. Paulo newspaper. The aim to discuss the emergence of the phenomenon and its features based on the concepts arised from the social theory of the scandal, proposed by John B. Thompson, in dialogue with the concept of social fields defined by Pierre Bourdieu. The object of study is related to the six political scandals involving six ministers dismissed in the first term of President Dilma Rousseffs government (2011) : Antonio Palocci (Ministry of Civil House), Alfredo Nascimento (Ministry of Transport), Wagner Rossi (Ministry of Agriculture), Pedro Novais (Ministry of Tourism), Orlando Silva (Ministry of Sports) and Carlos Lupi (Ministry of Labour). The analyze is based on the Depth Hermeneutics methodology proposed by John B. Thompson in the book Ideology and Modern Culture (1990). The study derives from four search categories: Scandal sequencial structure, Source of the revelations, Prevalence of the scandal in the newspaper edition and Construction of the involved's profiles

A presente dissertação analisa a construção do escândalo político midiático no discurso jornalístico da Folha de S Paulo. A proposta é discutir a emergência e características do fenômeno a partir dos conceitos oriundos da teoria social do escândalo, proposta por John B. Thompson, em diálogo com a noção de campos sociais definida por Pierre Bourdieu. São objeto de estudo os escândalos envolvendo seis ministros demitidos no primeiro ano do primeiro mandato da presidente Dilma Rousseff (2011): Antonio Palocci (Ministério da Casa Civil), Alfredo Nascimento (Ministério dos Transportes), Wagner Rossi (Ministério da Agricultura), Pedro Novais (Ministério do Turismo), Orlando Silva (Ministério do Esporte) e Carlos Lupi (Ministério do Trabalho). A análise dos objetos de pesquisa foi baseada na metodologia da Hermenêutica de Profundidade, conforme proposta por John Thompson na obra Ideologia e Cultura Moderna. Serviram como ponto de partida para o estudo as seguintes categorias de análise: Estrutura sequencial do escândalo, Origem das revelações, Prevalência do escândalo frente ao conteúdo da edição e Construção do perfil dos envolvidos no escândalo
The construction of midiatic political scandal in Folha de S. Paulo: a analyze of the six scandals involving ministers from Dilma Rousseff government's first term
Keywords: Jornalismo; Comunicação; Ciência política; Calúnia e difamação; Journalism